SHAME STORM. - Andrews, Helen (First Things: A Monthly Journal of Religion & Public Life, 2019)
The article presents the author's insights about online and public shaming. Topics include the forced resignation of Ian Buruma as editor of the magazine "New York Review of Books," a celebrity fashion blog called Go Fug Yourself, and Ryan Holiday's memoir "Trust Me, I'm Lying: Confessions of a Media Manipulator."